Training Undergraduate Medical Students in Shared Decision Making: A Systematic Review - Shrivastava Prateek Saurabh; Bankar Nandkishor; Bandre Gulshan; Mishra Vaishnavi (Wolters Kluwer Medknow Publications, 2024)
In the field of healthcare delivery, shared decision making (SDM) refers to a collaborative process, wherein both patients and the healthcare professionals mutually work to make informed and consensus decisions with reference to the kind of medical care that will be administered to patients. The purpose of the current review is to explore SDM in health care, ascertain the role of medical education, and identify the ways to train and assess undergraduate medical students in competencies pertaining to SDM. An extensive search of all materials related to the topic was carried out on the PubMed and Google Scholar search engines and a total of 29 articles were selected based on their suitability with the current review objectives and analyzed. Keywords used in the search include learning resources in the title alone only (viz. shared decision making [ti] AND patient [ti]; shared decision making [ti] AND medical education [ti]; shared decision making [ti] AND assessment [ti]; shared decision making [ti] AND self-assessment [ti]; shared decision making [ti]; shared decision making [ti]). In the domain of medical education, the promotion of SDM essentially will require a multipronged approach to enable its integration into the medical curriculum. However, we must remember that mere teaching-learning methods would not improve it unless they are supplemented with assessment methods, otherwise, we will fail to deliver sustained results. In conclusion, SDM in medical education and healthcare industry represents a transformative shift from the traditional paradigm to a patient-centered approach that empowers both patients and healthcare providers, including budding medical students. The need of the hour is to advocate and encourage structured integration of SDM in the medical curriculum and support the same with periodic assessments.